2013
DOI: 10.1371/journal.pone.0064101
|View full text |Cite
|
Sign up to set email alerts
|

High Doses of Ursodeoxycholic Acid Up-Regulate the Expression of Placental Breast Cancer Resistance Protein in Patients Affected by Intrahepatic Cholestasis of Pregnancy

Abstract: BackgroundUrsodeoxycholic acid (UDCA) administration in intrahepatic cholestasis of pregnancy (ICP) induces bile acids (BA) efflux from the foetal compartment, but the molecular basis of this transplacental transport is only partially defined.AimTo determine if placental breast cancer resistance protein (BCRP), able to transport BA, is regulated by UDCA in ICP.Methods32 pregnant women with ICP (14 untreated, 34.9±5.17 years; 18 treated with UDCA - 25 mg/Kg/day, 32.7±4.62 years,) and 12 healthy controls (33.4±3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
2
4
0
Order By: Relevance
“…However, no involvement of FXR was observed. Azzaroli et al (2013) reported that UDCA is not an effective ligand for nuclear receptor FXR, which is in line with our current data . This could be due to several reasons: (1) UDCA is a weak agonist to FXR that may explain the noninvolvement of FXR in this study and (2) could be due to the organ specific FXR mRNA expression, low level of mRNA for FXR in the heart but high expression in the kidney and adrenal gland.…”
Section: Discussionsupporting
confidence: 88%
“…However, no involvement of FXR was observed. Azzaroli et al (2013) reported that UDCA is not an effective ligand for nuclear receptor FXR, which is in line with our current data . This could be due to several reasons: (1) UDCA is a weak agonist to FXR that may explain the noninvolvement of FXR in this study and (2) could be due to the organ specific FXR mRNA expression, low level of mRNA for FXR in the heart but high expression in the kidney and adrenal gland.…”
Section: Discussionsupporting
confidence: 88%
“…The abundance of this protein was further increased in the placenta of ICP patients treated with standard doses of UDCA. Enhanced expression of placental ABCG2 has been found previously in ICP patients treated with high doses of UDCA [28]. The fact that mRNA was not enhanced in the UDCA treated group suggests that mechanisms other than transcription were involved.…”
Section: Concentration (Mm)supporting
confidence: 53%
“…To determine whether the beneficial effect of UDCA involved an enhancement of the placental barrier for bile acids and PMS, changes in the expression of OATP1B3, main responsible for bile acid transport into the placenta [26], as well as the export pumps which have been suggested to play a role in the hepatobiliary function of the placenta [13,16,27,28] were investigated. Relative SLCO1B3 mRNA levels determined by quantitative PCR in control, ICP and ICP+UDCA placentas were similar, as shown in Table 4.…”
Section: Effect Of Icp and Udca Treatment On The Placental Barrier Fomentioning
confidence: 99%
“…A higher concentration (10 μM) of PhIP decreased expression of BCRP while the mRNA levels were upregulated both at lower (1 μM) and higher concentrations (10 μM) (233). Ursodiol (ursodeoxycholic acid, the drug of choice for intrahepatic cholestasis in pregnancy) was shown to cause an increase in the expression of BCRP at the mRNA and protein level thus causing an efflux of bile acids from the fetal side (234). Recently, Jebbink et al studied the relation between placental transport of bile acids and ABCG2 expression in preeclamptic pregnancies complicated by hemolysis elevated liver enzymes and low platelets and found that the lower levels of bile acids in the fetal compartment compared to maternal levels is not related with the placental ABCG2 expression levels (235).…”
Section: Abc Transporters In the Placentamentioning
confidence: 99%